Corporate governance, financial management decisions and firm performance: Evidence from the maritime industry - Louca, Christodoulos; Panayides, Photis; Andreou, Panayiotis (My University, 2014)
This study investigates the relation between corporate governance with (i) financial management decisions such as earnings management and sub-optimal investment, and (ii) firm performance in maritime firms. The study reveals that important corporate governance measures, such as insider ownership, board size, presence of corporate governance committees, the percentage of directors serving on the boards of other firms and CEO duality, are associated with financial management decisions and firm performance. The associations revealed can potentially assist in mitigating agency problems and improving financial management decisions and performance in maritime firms.
Keywords: Corporate governance; Earnings management; Firm performance; Maritime firms; Sub-optimal investment